Bamboo Fiber as Enhancement Material in Concrete - Roszanihar, Muhammad hazman shafiq; Abdullah, Mohd Sufyan (Progress in Engineering Application and Technology, 2023)
Bamboo is one of Malaysia’s most frequently practiced agriculture plant that can get easily. Bamboo grows in both tropical and subtropical climates. Due to their economical cost, now bamboo is usually being used as structural system. The objective of the study is an important aspect that need to be focus on. This is because it is the objective that determines the direction of the study. To formulate and determine the workability of the reinforcement concrete mixture of adding the bamboo fiber and determine compressive strength and tensile characteristics bamboo fiber in reinforcement concrete. This study focuses on the identification of using bamboo fiber in the concrete and it will be tested following the standard test of concrete that testing to determine the properties of the concrete after mixing it with bamboo fiber. The ratio of the bamboo fiber that being use in reinforcement concrete is determine by specific range, for the length of fiber is 30mm and the quantity being used in the ratio of concrete is 0%, 0.1%, 0.2%, and 0.3%. The concrete sample need for this test is 36 sample, that is 24 cube sample size and 12-cylinder sample size. It can be concluded that bamboo is a sustainable plant-based material that can help in revolutionaries the construction industries to the next level of construction that can be more considerable as green construction